Computer-aided design, manufacturing, modeling and simulation : selected, peer reviewed papers from the International Conference on Computer-Aided Design, Manufacturing, Modeling and Simulation (CDMMS 2011), September 13-16, 2011, Hangzhou, China - He, Xingui (Applied mechanics and materials ;, 2011)
The aim of this special volume was to facilitate the exchange of information concerning the best practices for CAD, CAM, Manufacturing, Mechanical Engineering, Modeling and Simulation, etc. It provided the opportunity for engineers and scientists in academia, industry, and government to address the most innovative research and developments, including technical challenges, social and economic issues, and to discuss ideas, results, work-in-progress and experience touching all aspects of Computer-Aided Design, Manufacturing, Modeling and Simulation. Review from Book News Inc.: The 140 papers sele.